Decentralisation and beyond: The impact of blockchain on global economies, banking, and governance - Sharma Mohit; Patidar Sanjay (Journal of Engineering Management and Competitiveness)
The Fourth Industrial Revolution has ushered in groundbreaking digital advancements across biology, materials science, and computing. Among these, blockchain technology emerges as a key innovation with the power to reshape economic systems and business operations. While blockchain offers solutions for critical digital needs such as user verification, data security, and intellectual property management, its widespread adoption remains constrained by a limited understanding of its benefits. This research explores two primary areas: the sustainability of crypto exchange systems and blockchain's governance implications in our digital economy. Moving beyond Bitcoin, the study examines blockchain from both broad economic perspectives and organisational levels, viewing blockchain-based entities as global institutions. It analyzes blockchain's potential as a decentralized governance tool, assessing how it creates value and enables effective governance while potentially preventing financial fraud. The study also compares different countries' approaches to cryptocurrency regulation. The research methodology combines two methods: a comprehensive review of academic blockchain literature and an analyses of blockchain community discussions. It also includes ethnographic research, examining the governance structures and challenges within DAOs (decentralised autonomous organisations).